An Ambrosia Beetle Xyleborus affinis Eichhoff, 1868 (Insecta: Coleoptera: Curculionidae: Scolytinae) - Lanette Sobel; Andrea Lucky; Jiri Hulcr (EDIS)
Xyleborus affinis is one of the most widespread and common ambrosia beetles in the world. It is also very common in Florida. Like other ambrosia beetles, it bores tunnels into the xylem of weakened, cut or injured trees and farms gardens of symbiotic fungus for food. Females lay eggs in the fungus-lined galleries and larvae feed exclusively on the fungi. Recent studies have shown that Xyleborus affinis can vector the fungus responsible for laurel wilt disease, which is lethal to numerous species of trees in the Lauraceae family. This 5-page fact sheet was written by Lanette Sobel, Andrea Lucky, and Jiri Hulcr, and published by the UF Department of Entomology and Nematology, June 2015. (Photo credit: Juri Hulcr, UF/IFAS)